Design of a Mathematical Learning Game Model for Elementary School in the Sumbang Banyumas Area - Qonita Rafida Hana; Ayu Wulandari (Universitas Amikom Purwokerto, 2023)
Mathematics is an exact science that forms the basis of other sciences so mathematics is interrelated with other sciences. If a child has been taught mathematics from an early age, then the child will easily enter other branches of science such as chemistry, physics, especially mathematics itself. The lack of aids and visual aids in schools makes it difficult for teachers or teachers to convey subject matter in class, so it is very difficult for teachers to provoke student concentration during teaching and learning activities, and sometimes students play alone when the teacher is delivering lessons in class. The purpose of this research is to make a math educational game for grade III elementary schools so that students can increase their concentration in learning, and help the learning process to be interactive and not boring. The method of collecting data from this thesis uses 3 methods, namely interviews, observation, and questionnaires. The system development method used in this study is the Multimedia Development Life Cycle (MDLC). From the results of the alpha test it showed that the functionality of the game that was made was successful and from the beta test it showed that 89.49% of student respondents answered strongly agreed and 76% of teacher respondents answered in agreement. It can be concluded that this game is feasible to be used as a learning aid for students in class.